2008
DOI: 10.1007/s10722-008-9400-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the pili nut genus (Canarium L., Burseraceae) and its cultivated species

Abstract: Seeds from species of Canarium L. (Burseraceae) have been recommended as a potential nut crop for global trade that, if adopted, would be the first 'new' nut commodity since the introduction of the Macadamia nut in the early 20th century. The present study addresses several knowledge gaps about the evolutionary biology of Canarium species in order to explore their phylogeny and cultivation history in greater detail. The phylogeny of select Canarium species (16 spp.) from the three taxonomic sections of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The amplification program used for ETS, ITS, psbA-trnH and trnL-trnF consisted of 5 minutes of initial denaturation at 95°C; 36 cycles of 1 minute denaturation at 95°C, 40 seconds of annealing at 53–54°C, an elongation of 40 seconds to 1 minute (depending on the length of the target sequence) at 72°C; and a final elongation for 5 minutes. A touchdown PCR program was used for the amplification of NIAi3 [34]. …”
Section: Methodsmentioning
confidence: 99%
“…The amplification program used for ETS, ITS, psbA-trnH and trnL-trnF consisted of 5 minutes of initial denaturation at 95°C; 36 cycles of 1 minute denaturation at 95°C, 40 seconds of annealing at 53–54°C, an elongation of 40 seconds to 1 minute (depending on the length of the target sequence) at 72°C; and a final elongation for 5 minutes. A touchdown PCR program was used for the amplification of NIAi3 [34]. …”
Section: Methodsmentioning
confidence: 99%
“…For the Melicope / Platydesma data set, four nuclear markers [ITS, external transcribed spacer (ETS), AT103 and NIAi3 ] and two plastid markers ( trnL–trnF and psbA–trnH ) were amplified by the polymerase chain reaction (PCR) using a standard protocol (see Appelhans et al ., ) with primer annealing temperatures of 51–55 °C for all markers except NIAi3. Amplification of NIAi3 followed a touchdown protocol (Weeks, ). Universal primers were used for amplification: ITS (ITS2, ITS3, ITS4, ITS5a; White et al ., ; Stanford, Harden & Parks, ); ETS (Bur1, 18S‐IGS; Baldwin & Markos, ; Becerra, ); AT103 (At103 forward, At103 reverse; Li et al ., ); NIAi3 (NIA3F, NIA3R; Howarth & Baum, ); trnL–trnF (c, d, e, f; Taberlet et al ., ); and psbA–trnH (psbA, trnH; Sang, Crawford & Stuessy, ).…”
Section: Methodsmentioning
confidence: 99%
“…Differences between the sequences are comparable to those found between alleles in Scaevola (Howarth and Baum, 2005), which, together with the absence of stop codons, would suggest that the versions are alleles rather than pseudogenes. At the same time, duplications of NIAi3 have been found in the tribe Canarieae within Burseraceae (Weeks, 2009), and in other families (Hamman-Khalifa et al, 2007;Yi et al, 2008), although the sequences found in B. simaruba did not correspond to those in Canarieae. Whether they represent alleles or paralogues with potential associated lineage sorting, in the genus these sequences seem to be restricted to B. simaruba (J.A.…”
Section: Congruence and Testing Membership In The Simaruba Complexmentioning
confidence: 97%